From jihad to terror: Deconstructing western media discourse on Islamism groups and its implications for global Muslim identity - Izazi Kasyfi (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: This research is based on the phenomenon of Islamophobia that occurs in global society until now due to the framing of Islam carried out by the Western world through its media. The purpose of this research is to reveal how the framing of Islam by Western media is constructed and to what extent that framing influences the identity of other Islamic groups as well as the identity of Islam itself in the public sphere. Methods: This research uses a descriptive qualitative approach using Entman’s Framing Analysis method. The data collection technique is carried out through documentary study by taking news from Western media such as Fox News, New York Post, The Telegraph, The Guardian and the results of previous research researchers in the form of statistical data related to media coverage of CNN, and BBC to then be analyzed. In addition, other data is taken from social media such as Instagram and YouTube. Findings: The results of the study indicate that following the September 11 attacks by Al Qaeda, Western media framing expanded antagonism from Al Qaeda to broader Islamic groups, such as Hamas, and ultimately to Islam itself. This framing was disseminated not only through news media but also via entertainment and social media, generating moral legitimacy to discriminate Muslims. Conclusion: This study confirms that Western media framing is systematically responsible for the emergence of Islamophobia which has an impact on the confidence of Muslims to display their religion or religious identity in public. Novelty/Originality of this article: This study implements the Framing Analysis method to analyze news from Western media in depth by applying Entman's four main elements, namely Problem Definition, Causal Interpretation, Moral Evaluation, and Treatment Recommendations. This method is effective in exploring framing efforts in news reporting in a scientific and easy to understand manner.